A bi-specific lectin from the mushroom Boletopsis grisea and its application in glycoanalytical workflows - Mehul B. Ganatra (Nature Portfolio, 2021)
Abstract The BLL lectin from the edible Japanese “Kurokawa” mushroom (Boletopsis leucomelaena) was previously reported to bind to N-glycans harboring terminal N-acetylglucosamine (GlcNAc) and to induce apoptosis in a leukemia cell line. However, its gene has not been reported. In this study, we used a transcriptomics-based workflow to identify a full-length transcript of a BLL functional ortholog (termed BGL) from Boletopsis grisea, a close North American relative of B. leucomelaena. The deduced amino acid sequence of BGL was an obvious member of fungal fruit body lectin family (Pfam PF07367), a highly conserved group of mushroom lectins with a preference for binding O-glycans harboring the Thomsen–Friedenreich antigen (TF-antigen; Galβ1,3GalNAc-α-) and having two ligand binding sites. Functional characterization of recombinant BGL using glycan microarray analysis and surface plasmon resonance confirmed its ability to bind both the TF-antigen and β-GlcNAc-terminated N-glycans. Structure-guided mutagenesis of BGL’s two ligand binding clefts showed that one site is responsible for binding TF-antigen structures associated with O-glycans, whereas the second site specifically recognizes N-glycans with terminal β-GlcNAc. Additionally, the two sites show no evidence of allosteric communication. Finally, mutant BGL proteins having single functional bindings site were used to enrich GlcNAc-capped N-glycans or mucin type O-glycopeptides from complex samples in glycomics and glycoproteomics analytical workflows.